2017
DOI: 10.1017/aer.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Emission prediction in conceptual design of the aircraft engines using augmented CRN

Abstract: The semi-analytical prediction of pollutants emissions from gas turbines in the conceptual design phase is addressed in this paper. The necessity of this work arose from an urgent need for a comprehensive model that can quickly provide data in the conceptual design phase. Based on the available inputs data in the initial phases of the design process, a chemical reactor network (CRN) is defined to model the combustion with a detailed chemistry. In this way, three different chemical mechanisms are studied for Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They conducted an experimental study in a gas turbine combustor and applied OH PLIF and POD to determine reasons for the frequency mode shift phenomenon (11) . Moreover, many researchers have studied the characteristics of combustion using experimental (12)(13)(14)(15)(16)(17)(18)(19)(20) , analytic (21,22) and computational (23)(24)(25) approaches.…”
Section: Past Research On H 2 /Ch 4 Combustion In Gas Turbinementioning
confidence: 99%
“…They conducted an experimental study in a gas turbine combustor and applied OH PLIF and POD to determine reasons for the frequency mode shift phenomenon (11) . Moreover, many researchers have studied the characteristics of combustion using experimental (12)(13)(14)(15)(16)(17)(18)(19)(20) , analytic (21,22) and computational (23)(24)(25) approaches.…”
Section: Past Research On H 2 /Ch 4 Combustion In Gas Turbinementioning
confidence: 99%
“…_ m fuel is fuel flow rate, LHV fuel is fuel lower heating value, and Y is mass fraction. Note that in equation (24) we ignore the heat loss from the combustor and only take into account the heat absorbed by the flow (i.e. combustor is assumed adiabatic).…”
Section: Ammonia Addition Effectsmentioning
confidence: 99%
“…This method showed acceptable reliability and was used in later studies. 13,22,2426 Xu et al 13 used this assumption to predict and validate NO x emission of a lean prevaporized premixed combustor. Saboohi and Ommi 24 predicted the CO and NO x emission of an annular combustor in different power settings using this assumption and showed relatively good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the NOx emission index strongly depended on the used mechanism. Saboohi and Ommi (2017) compared the three mechanisms of Ranzi et al (2012), GRI-Mech.3.0 and Kollrack (Mattingly, 2002) based on temperature variations and NO and CO molar ratios in a PSR. They specified that the mechanism of Ranzi offered the best results, but due to the increase in the number of species and chemical reaction steps, the computation costs increased significantly.…”
Section: Kinetics In Chemical Reactor Networkmentioning
confidence: 99%